PENGARUH SISTEM MANAJEMEN ISO 9001:2008 TERHADAP PELAYANAN KEFARMASIAN PUSKESMAS DI KABUPATEN SLEMAN - , MUCH ILHAM NOVALISA AJI WIBOWO; , Prof. Dr. Dra. Sri Suryawati,Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : The vision of health development organized by the district health center is achieving district healthy. The need for improving the quality of health services in health centers contained in the WHO Annual Report 2008 under the title "Primary Health Care, Now More Than Ever". The efforts to improve the quality of services in health centers is ISO 9001:2008 certification at the international level. ISO 9001 certification is expected to improve the quality of pharmacy services at health centers. In order to ensure the implementation of quality management system certification ISO 9001:2008 in Sleman district health centers especially in pharmaceutical services, we need a special evaluation of pharmacy services at existing health centers and Sleman district that have not implemented ISO 9001:2008. Purpose : The purpose of this study is to describe the influence of ISO 9001:2008 quality management system for pharmacy services at district Sleman health centers who have and have not implemented the ISO 9001:2008. Method : The study design is a descriptive cross-sectional design. Data captured includes quantitative data from observations of pharmacy services at the health center and qualitative data from in-depth interviews. The study period October 23, 2012 until December 23, 2012. Result : The results showed Score adherence to standard operating procedures at the clinic ISO and non-ISO is 1.25 and 1. Average preparation time for non-drug concoction and concoction at ISO puskemsas sequence was 383 seconds and 193 seconds. average preparation time mixing and non-mixing drugs in health centers in order are non ISO 446 seconds and 193 seconds. Average delivery time ISO medicine in health centers is 87 seconds, the average time on the drug delivery centers are non-ISO 60.75 seconds. Percentage suitability prescription drugs in health centers and ISO and non ISO is 100% and 99.98%. The percentage of drugs in health centers completeness label ISO and non ISO is 100% and 100%. The percentage of patients in the clinic knowledge of ISO and non-ISO is 84.97% and 72.47%.. The levels of patient satisfaction in ISO and non ISO clinic in category "Satisfied". Conclusion : The policy of Quality Management System ISO 9001:2008 that applied to the community health center in Sleman district does not affect the improvement of pharmaceutical services at the community health center. The observations indicate that the quality was not much different in the two types of community health center, it makes an ISO 9001:2008 should be reviewed.